Program Edukasi Kesehatan Berbasis Keluarga pada Self-Management Pasien Hipertensi - Zahirah, Esa; Pahria, Tuti; Kurniawan, Titis (Journal of Telenursing (JOTING), 2023)
This research aims to examine further how families are involved in family-based self-management education for hypertension sufferers. The method used is a scoping review with PCC (Population, Context & Concept) components. Population is "hypertension", Context is "self-management" Concept is "family-based oriented". This scoping review is aimed at answering the question "what and what forms of family-based self-management education for hypertension sufferers, compliance with treatment plans and providing care support for patients." The results of this research obtained 369 articles through searches using several databases consisting of PubMed, Science Direct and CINAHL, resulting in 5 articles analyzed in the research. The conclusion of this research is that mapping self-management interventions for hypertensive patients involving families plays an important role in improving self-management in hypertensive sufferers. Keywords: Family, Hypertension, Self-Management Behavior